Is China buying the world? - Nolan, Peter 1949- (Cambridge, [England] Polity Press, 2012)
China has become the world's second biggest economy and its largest exporter. It possesses the world's largest foreign exchange reserves and has 29 companies in the FT 500 list of the world's largest companies. 'China's Rise' preoccupies the global media, which regularly carry articles suggesting that it is using its financial resources to 'buy the world'. Is there any truth to this idea? Or is this just scaremongering by Western commentators who have little interest in a balanced presentation of China's role in the global political economy? In this short book Peter Nolan - one of the leading international experts on China and the global economy - probes behind the media rhetoric and shows that the idea that China is buying the world is a myth.
Keywords: Investments, Chinese; China -- Foreign economic relations